The Construction of Ecological Security Pattern under Rapid Urbanization in the Loess Plateau: A Case Study of Taiyuan City - Qiong Qiao; Zhilei Zhen; Liming Liu; Pingping Luo (Remote Sensing, 2023)
Taiyuan City in the eastern Loess Plateau has experienced severe ecological problems caused by urban expansion. For cities undergoing rapid urbanization, building an ecological security pattern (ESP) is an effective means to improve urban resilience. Here, geographic information systems (GIS) were used to analyze, manipulate, and visualize urban ecological multi-source information and remote sensing (RS) for the history of land use/land-cover (LULC) changes and the structure of the urban ecological system. Four important ecosystem service functions were estimated: soil conservation, habitat quality, water yield, and carbon storage. The minimum cumulative resistance (MCR) model was combined with the circuit theory method to determine the ecological corridors, pinch points, and barrier points. Our results showed that: (1) from 1980 to 2020, Taiyuan’s built-up area showed increased construction land and enhanced landscape fragmentation. The decline in cultivated land was mainly attributed to construction land. During the period from 2000 to 2010, a greater amount of land was changed in Taiyuan than in other periods; (2) The ecosystem service evaluation based on the LULC in 2020 revealed that the central urban area was lower than the other areas; (3) 38 ecological source sites were identified, accounting for 16% of the total study area. An area of 106 km2 was allocated to construct 79 ecological corridors. We identified 31 ecological pinch points and 6 ecological barrier points; (4) an ESP optimization governance model of “two rings, four zones, and nine corridors” was proposed. Our study provides theoretical guidance for sustainable development and ecological design in Taiyuan City and other regions.